(untitled) (ArtCultura, 2008)
Desde que o Brasil adotou a pauta neoliberal, toda a produção cultural passou a ser rigorosamente determinada pelos interesses de mercado e o próprio Estado curvou-se às exigências do Capital. O teatro paulista foi o primeiro setor a reagir ao desastre, criando o movimento "Arte contra a barbárieâ€? para tentar contrapor-se ao processo. Este texto procura dar conta de alguns aspectos de sua intervenção. PALAVRAS-CHAVE: teatro de grupo; mercado; produção cultural. ABSTRACT Since Brazil has adopted neoliberal politics, all cultural production became strictly defined by the market and the State itself has been totally bowed to Capital demands. At São Paulo, the first reaction against the disaster came from theater groups. They created a movement named "Art against barbarismâ€? aiming to confront this policy. This text tries to make a brief account of some aspects of their reasons and actions. KEYWORDS: theater groups; market; cultural production.